2018
DOI: 10.5937/ekonomika1801001s
|View full text |Cite
|
Sign up to set email alerts
|

Information and communication technologies product market and protection of competition in the Republic of Serbia

Abstract: Starting from the fact that the importance of information and communication technologies (ICT) for the development of a national economy is high, it has been examined how this sector and the situation in individual markets in the sector affect competition policy. All the most important markets of the ICT sector of Serbia are characterized by a high level of concentration measured using the Herfindahl-Hirschman Index (HHI) with a tendency of decrease. In such circumstances, there are three directions of changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…To assess future responses competition policy, Stojanović and Kostić (2018) analysed the level of concentration in selected markets of electronic communications services of the Republic of Serbia using the Herfindahl-Hirschman Index from 2007 to 2016. They concluded that the concentration level is extremely high but with a declining trend.…”
Section: Conditions In the Global Electronic Communications Marketmentioning
confidence: 99%
“…To assess future responses competition policy, Stojanović and Kostić (2018) analysed the level of concentration in selected markets of electronic communications services of the Republic of Serbia using the Herfindahl-Hirschman Index from 2007 to 2016. They concluded that the concentration level is extremely high but with a declining trend.…”
Section: Conditions In the Global Electronic Communications Marketmentioning
confidence: 99%